Mali : Technical Assistance Report. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Assistance Report surveys the resources of the subnational jurisdictions and proposes a tax reform strategy for Mali. In Mali, the system of local taxes generates insufficient revenue and relies on obsolete taxes, which are particularly difficult to collect. It proposes that the rental value be replaced by a value per hectare indexed on various factors such as access to property or public services; geographic location; and average and georeferenced consumption of electricity, water, cell phone minutes. A real property tax system will also require the elimination of key exemptions under the current real property tax.